2017
DOI: 10.1104/pp.17.00828
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Potentiation of Fatty Acid and Triacylglycerol Accumulation

Abstract: Photosynthetically derived sugar provides carbon skeletons for lipid biosynthesis. We used mutants of Arabidopsis (Arabidopsis thaliana) and the expression of oleogenic factors to investigate relationships among sugar availability, lipid synthesis, and the accumulation of triacylglycerol (TAG) in leaf tissue. The adg1 mutation disables the small subunit of ADP-glucose pyrophosphorylase, the first step in starch synthesis, and the suc2 mutation disables a sucrose/proton symporter that facilitates sucrose loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 49 publications
5
40
1
Order By: Relevance
“…Similar observations have been reported in A. thaliana, tobacco and sugarcane, suggesting both genes can act as key drivers for TAG biosynthesis in both dicot and monocot species (Kelly et al, 2013;Vanhercke et al, 2013;Zale et al 2016). We compared two different monocot promoters as previous studies in tobacco and A. thaliana had suggested promoter strength to be critical when co-expressing WRI1 and DGAT2a transgenes (Vanhercke et al, 2014;Zhai et al, 2017). Unlike tobacco and A. thaliana, it appears that at least sugarcane and sorghum can tolerate strong constitutive promoters to drive combined WRI1 and DGAT expression.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar observations have been reported in A. thaliana, tobacco and sugarcane, suggesting both genes can act as key drivers for TAG biosynthesis in both dicot and monocot species (Kelly et al, 2013;Vanhercke et al, 2013;Zale et al 2016). We compared two different monocot promoters as previous studies in tobacco and A. thaliana had suggested promoter strength to be critical when co-expressing WRI1 and DGAT2a transgenes (Vanhercke et al, 2014;Zhai et al, 2017). Unlike tobacco and A. thaliana, it appears that at least sugarcane and sorghum can tolerate strong constitutive promoters to drive combined WRI1 and DGAT expression.…”
Section: Discussionsupporting
confidence: 54%
“…We compared two different monocot promoters as previous studies in tobacco and A. thaliana had suggested promoter strength to be critical when co‐expressing WRI1 and DGAT2a transgenes (Vanhercke et al ., ; Zhai et al ., ). Unlike tobacco and A. thaliana , it appears that at least sugarcane and sorghum can tolerate strong constitutive promoters to drive combined WRI1 and DGAT expression.…”
Section: Discussionmentioning
confidence: 97%
“…To test the influence of endogenous sugar content on fatty acid and TAG accumulation, we generated a high-leaf-sugar mutant by simultaneously restricting sucrose phloem loading and blocking starch synthesis by crossing the suc2 (encoding a Suc/H + symporter that loads Suc into phloem) mutant (Srivastava et al, 2008) and an adg1 mutant (Lin et al, 1988). The sugar content (combined Glc and Suc) in adg1 suc2 leaves was 80-fold higher than that of the wild type, and TAG accumulation increased more than 10-fold with respect to the wild type to 1% of dry weight, demonstrating a strong positive relationship between sugar accumulation and TAG accumulation (Zhai et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Sanjaya et al (2011) also observed that the expression of WRI1 in seedling of AGP-deficient lines is increased compared with the wild type. However, in the Arabidopsis adg1 suc2 mutant, WRI1 expression is not significantly different from the wild type, but the abundance of the WRI1 protein is increased due to its stabilization (Zhai et al, 2017b). Sugar-dependent regulation of WRI1 expression and WRI1 protein stability implies that sugar signaling is involved in regulating lipid (TAG) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid (FA) and triacylglycerol (TGA) biosynthesis requires that Suc is abundant and biosynthetic pathways are activated by sugar signaling. Zhai et al (2017) achieve significant increases in FA and TGA content with genotypes defective in starch biosynthesis and the export of sugar from leaves. Contents of these lipid molecules were further bolstered by overexpression of three genes associated with the "push," "pull," and "protection" stages of lipid synthesis and accumulation (Vanhercke et al, 2014).…”
Section: Energy Nexus: Dynamic Sugar Sensing Meters Carbon Allocationmentioning
confidence: 99%